Collaborative Governance in Countering Drug Control in Makassar City - Yamin, Muhammad Nur; Hidayat, Nur Ihsan; ., Sulmiah (KnE Social Sciences, 2024)
This study seeks to determine how collaborative governance has been implemented in Makassar City’s drug prevention efforts. This study employs a qualitative, descriptive methodology. Observation, interviews, and documentation are methods for collecting data. In Yin’s case study pattern matching model, the data analysis technique is used. The results demonstrated leadership facilitation, with each collaborating actor demonstrating a dependable capacity for activity implementation and problem-solving. Each organization has a decision-maker and policy-maker in charge. In institutional institutions, the division of roles and responsibilities is specified in the Cooperation Agreement. In the process of collaboration, formal and informal communication channels are established to foster mutual trust, and each party’s Cooperation Agreement guides the implementation of collaboration. The true outcome of collaborative action is the achievement of the program goals of each government agency, the community, and the private sector, as well as reducing drug use in Makassar City. The outcomes indicated that Anshel and Gash’s Collaborative Government model was suitable for the drug prevention program in Makassar City. In institutional institutions, Anshel and Gash’s CG mode necessitates the creation of a more detailed Standard Operating Procedure (SOP) because the rules in collaboration only refer to the Cooperation Agreement. Keywords: collaborative governance, drug control, collaboration actors